Pengaruh Efikasi Diri terhadap Kesiapan Kerja Lulusan Baru di Kota Bandung pada Masa Pandemi Covid-19 - Aldilanur Balqis Prisrilia; Lisa Widawati (Bandung Conference Series: Psychology Science, 2021)
Abstract. Currently, a lot of research on the internal factors that affect Work Readiness in Indonesia has been carried out. However, studies on internal factors that affect Work Readiness for fresh graduates during the COVID-19 pandemic are still minimal in Indonesia. The purpose of this study was to determine whether there was an effect of self-efficacy on Work Readiness Fresh graduates in Bandung City during the Covid-19 Pandemic. The subjects in this study were 145 fresh graduates in the city of Bandung who had just graduated during the covid-19 pandemic. The measuring instrument used in this study is the GSE from Matthias Jerusalem and Ralf Schwarzer with reliability ranging from 0.47 to 0.75 and the Work Readiness measuring instrument from Caballero which has been adapted into Indonesian by Sinndy Fitriani with a reliability of 0.96. The analysis technique in this study uses simple linear regression analysis with the help of SPSS software. Based on the results of the data analysis, this study shows that self-efficacy has a significant effect on work readiness with a coefficient of determination of 35.5%, while the remaining 64.5% is influenced by other variables not examined in this study. Abstrak. Saat ini penelitian mengenai faktor-faktor internal yang mempengaruhi Work Readiness di Indonesia sudah banyak dilakukan. Namun studi mengenai faktor internal yang mempengaruhi Work Readiness pada fresh graduate di masa pandemi covid-19 masih minim dilakukan di Indonesia. Tujuan dari penelitian ini adalah untuk mengetahui apakah terdapat pengaruh self efficacy terhadap Work Readiness Fresh graduate di Kota Bandung Pada Masa Pandemi Covid-19. Subyek dalam penelitian ini adalah 145 fresh graduate di Kota Bandung yang baru lulus pada masa pandemi covid-19. Alat ukur yang digunakan dalam penelitian ini adalah GSE dari Matthias Jerusalem dan Ralf Schwarzer dengan reliabilitas berkisar antara 0,47 hingga 0,75 serta alat ukur Work Readiness dari Caballero yang telah diadaptasi ke dalam Bahasa Indonesia oleh Sinndy Fitriani dengan reliabilitas sebesar 0,96. Teknik analisis dalam penelitian ini menggunakan analisis regresi linier sederhana dengan bantuan software SPSS. Berdasarkan hasil analisis data tersebut, penelitian ini menunjukkan bahwa Self-efficacy berpengaruh signifikan terhadap work readiness dengan koefisien determinasi sebesar 35,5%, sedangkan sisanya sebesar 64,5% dipengaruhi oleh variabel lain yang tidak diteliti pada penelitian ini.